Psycho-behavioural influences on vaccine success: towards a brief, non-pharmacological primary care intervention - Ayling, Kieran (2017)
Vaccines against infectious diseases are less effective in older adults than in younger adults. This is of significant clinical importance as older adults are also the most vulnerable to contracting, and suffering the most severe consequences of, infectious diseases. Prior research demonstrates that behavioural and psychological factors can modulate the immune system and, in turn, influence how well vaccines work. However, there is a relative paucity of work focusing on older adults. Further, studies have tended to consider only one behavioural or psychological factor at a time - meaning it is unclear which factor, or combination of factors, should be the target of interventions to enhance vaccine effectiveness. This thesis presents three distinct, yet inter-related, pieces of original research which sought to further our understanding of the behavioural and psychological influences on vaccinations and inform the future development of interventions to enhance vaccine effectiveness.